PSYCHOLOGICAL AND ETHICAL PERSPECTIVES ON VIOLENCEBASED DISCIPLINARY ACTION IN SCHOOLS - Wajid Nail Jayyid Almahdi; Muhammad Maulana; Musdalifah Adilah; Sri Rahayu Ningsih (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
Psychological and Ethical Perspectives on Violence-Based Disciplinary Practices in Schools. Violence in student discipline remains an ethical and psychological concern in Indonesian schools. Teachers often enforce discipline through physical or verbal punishment, which harms students’ emotional well-being and violates professional ethics. This study applied a systematic literature review by analyzing 10 articles published between 2015-2024 from national and international databases. The review identified four key themes: ethical dilemmas in school discipline, psychological impacts of violence on students, teachers’ emotional regulation gaps, and the need for empathy-based non-violent discipline. It concludes that violence-based discipline contradicts character education and humanistic values. A paradigm shift toward humanistic discipline through ethical literacy and emotional intelligence training for teachers is urgently needed.